Analisis mobilitas pembawa muatan pada lucutan plasma korona positif konfigurasi kawat silinder menggunakan gas nitrogen - Victor Prima Saputra; Muhammad Nur (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
Research on mobility of charge carries in positive corona plasma have been done by using a cylindrical wire configuration and nitrogen gas field. Plasma reactor that used in this research is a stainless tube with a length of 24 cm and a diameter of 3.5 cm. The characterization of current and voltage is used to determine the value of charge carrier mobility. This characterization was performed using nitrogen gas field. The voltage variation used was 0-11 kV with an increase interval of 0.3 kV and the flow of Nitrogen flow of 2-6 L / min with an increase interval of 1 L / min. From the research for positive corona obtained the highest charge carrier mobility at flow rate 2 L/minute equal to 0.115 ( m^2)⁄Vs and lowest charge carrier mobility at flow rate 3 L/minute equal to 0.0413 ( m^2)⁄Vs. At flow rate 2 L/minute the mobility between positive and negative corona have significant difference of 0.115 ( m^2)⁄Vs and 0.459 ( m^2)⁄Vs then decreased until finally at the gas flow rate 6 L/minute of positive coronas and negative corona have equal charge carrier mobility of 0.093 ( m^2)⁄Vs.Keywords: Plasma corona, characteristic current-voltage, the mobility of the charge-carriers, voltage, current